2017
DOI: 10.1016/j.appet.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of the affect regulation model of binge eating

Abstract: There is research suggesting that binge eating may serve an affect regulation function. However, experimental evidence supporting this model in adults is sparse and studies have been mixed regarding whether negative affect impacts objective energy intake. This study examined the impact of a real-time interpersonal stressor on laboratory test meal intake between individuals endorsing recent objective binge eating (≥1x/week) and those denying disordered eating. Generalized linear modeling was used to compare ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…Prior studies have shown that state negative affect is linked with subsequent LOC eating [25, 7073] and palatable food intake [26, 74]. However, we found only pre-meal state anxiety, but not state, anger, confusion, depression or fatigue, explained the relationship between recent social stress and palatable food intake.…”
Section: Discussioncontrasting
confidence: 81%
“…Prior studies have shown that state negative affect is linked with subsequent LOC eating [25, 7073] and palatable food intake [26, 74]. However, we found only pre-meal state anxiety, but not state, anger, confusion, depression or fatigue, explained the relationship between recent social stress and palatable food intake.…”
Section: Discussioncontrasting
confidence: 81%
“…Several theories suggest that binge eating functions as a maladaptive method of coping with or avoiding negative affective states (Heatherton & Baumeister, 1991; Polivy & Herman, 1993). As a result, emotional functioning disturbances are common among individuals who engage in binge eating, and the salience of negative affect in binge eating has been supported in numerous studies across a range of samples and research methodologies (Chua, Touyz, & Hill, 2004; Hudson et al, 2007; Russell, Haynos, Crow, & Fruzzetti, 2017; Smyth et al, 2007). Importantly, research investigations have shown that increased binge eating is associated with more psychological distress and disturbances in mood (Didie & Fitzgibbon, 2005; Mason & Lewis, 2014; Pinaquy et al, 2003).…”
Section: Negative Affect Restraint and Binge Eatingmentioning
confidence: 99%
“…Although these studies supported the interpersonal model using cross-sectional data, only longitudinal data can reveal and inform the casual relations inherent in mediational models (Maxwell, Cole, & Mitchell, 2011;Cole & Maxwell, 2003;Maxwell & Cole, 2007). Two experimental studies to date have tested the model in a temporally sensitive way (Russell, Haynos, Crow, & Fruzzetti, 2017;Shank et al, 2017). Female adolescents with loss of control eating completed assessments of recent social stress and negative affect, then consumed lunch from a multi-item laboratory test meal; in line with the interpersonal model of binge eating, findings revealed that pre-meal state anxiety mediated the relation between recent social stress and palatable food intake (Shank et al, 2017).…”
Section: Empirical Support For the Interpersonal Model Of Binge Eatingmentioning
confidence: 99%
“…Female adolescents with loss of control eating completed assessments of recent social stress and negative affect, then consumed lunch from a multi-item laboratory test meal; in line with the interpersonal model of binge eating, findings revealed that pre-meal state anxiety mediated the relation between recent social stress and palatable food intake (Shank et al, 2017). In another laboratory test meal study, researchers examined the effect of a real-time interpersonal stressor on negative affect and binge eating in a sample of individuals who endorsed recent regular binge eating, and findings suggested that over-consumption or under-consumption of food (i.e., "extreme intake") was triggered by laboratory-induced interpersonal stress in individuals who binge eat (Russell et al, 2017).…”
Section: Empirical Support For the Interpersonal Model Of Binge Eatingmentioning
confidence: 99%